EFFECT OF KORRA (Setaria italica) CROP RESIDUES INCORPORATION ALONG WITH MICROBIAL CONSORTIA ON HUMIC ACID, FULVIC ACID CONTENT IN SOIL AND PERFORMANCE OF CHICKPEA (Cicer arietinum) - A.J. SUVARNA LATHA; P. RATNA PRASAD; N.TRIMURTULU (The Journal of Research ANGRAU, 2023)
The field experiment was conducted on the clay soils of Agricultural Research Station, Amaravathi, Guntur between rabi 2017-18 and 2018-19 to find out the influence of crop residues on soil biological activity, growth and yield of chickpea under rainfed agro-climatic condition of Krishna zone. The korra crop residue was incorporated in the soil 45 days before sowing of chickpea either alone or in combination with microbial consortia and starter dose of N and P fertilizers as decomposition accelerators. Humic acid and fulvic acid assayed at different crop growth stages of chickpea got significantly increased by the application of crop residue along with microbial consortia. The drymatter accumulation at different growth stages and grain yield of chickpea were significantly influenced by the treatments. Among the treatments, the highest drymatter accumulation and grain yield of chickpea were recorded with 100 percent RDF(20:50:0:40) and was at par with the treatment T7, which received crop residue @1.5 t ha-1+ Microbial consortium@2 kg t-1+ urea 3 kg t-1 + SSP 15 kg t-1 of residue incorporated to soil during both the years of the experimentation. There was a significant positive correlation between humicacid and fulvic acid content with drymatter production of chickpea.